The Relationship Between the Duration of Preschool Education and Primary School Readiness - POLAT, ÖZGÜL (Routledge, 2016)
Early childhood experiences have a great effect on the course of a child's life. Preschool education can offer benefits for children, particularly those who do not have advantages at home, including benefits related to academic skills, social-emotional development, and communication. Thus, preschool experiences are a potential key to improving school readiness, especially among disadvantaged populations. One outcome of preschool education of interest to educators and families alike is the effect of such experiences on young children's self-concept and self-esteem. This study from Turkey paid particular attention to the effect of the length of time a child spends in preschool attendance on self-concept and school readiness. ©, Copyright Association for Childhood Education International.